2012
DOI: 10.1186/1471-230x-12-107
|View full text |Cite
|
Sign up to set email alerts
|

Higher frequency of cagA EPIYA-C Phosphorylation Sites in H. pylori strains from first-degree relatives of gastric cancer patients

Abstract: BackgroundTo evaluate the prevalence of more virulent H. pylori genotypes in relatives of gastric cancer patients and in patients without family histories of gastric cancer.MethodsWe evaluated prospectively the prevalence of the infection by more virulent H. pylori strains in 60 relatives of gastric cancer patients comparing the results with those obtained from 49 patients without family histories of gastric cancer. H. pylori status was determined by the urease test, histology and presence of H. pylori ureA. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…The risk for the development of gastric cancer in patients with a family history of gastric cancer has been reported to be as high as 1.6-2.6 folds (Kondo et al, 2003;Kawasaki et al, 2007). The recent literature have proved that relatives of gastric cancer patients are more frequently colonized by the most virulent H pylori cagA and vaculating cytotoxin (vacA) genotypes, which may increase their risk of gastric cancer when act together with genetic factors (Queiroz et al, 2012). In this content, the observed higher incidence of gastric cancer in family members in this study may provide some confirmation of the presence of a genetic link between the H pylori infection and gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk for the development of gastric cancer in patients with a family history of gastric cancer has been reported to be as high as 1.6-2.6 folds (Kondo et al, 2003;Kawasaki et al, 2007). The recent literature have proved that relatives of gastric cancer patients are more frequently colonized by the most virulent H pylori cagA and vaculating cytotoxin (vacA) genotypes, which may increase their risk of gastric cancer when act together with genetic factors (Queiroz et al, 2012). In this content, the observed higher incidence of gastric cancer in family members in this study may provide some confirmation of the presence of a genetic link between the H pylori infection and gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that individuals infected with H pylori have more than two-fold increased risk of developing gastric cancer compared with noninfected ones (Queiroz et al, 2012). Moreover, several studies have shown an increased risk of developing gastric cancer in relatives of patients with the infection (Brenner et al, 2000;Queiroz et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The cagA PCR was performed by Batista et al (2011). The reactions yielded products of 500-850 bp as follows: EPIYA AB, 500 bp; EPIYA-ABC, 640 bp; EPIYA-ABCC, 740 bp; and EPIYA-ABCCC, 850 bp (Queiroz et al, 2012).…”
Section: Detection Of Caga Epiyamentioning
confidence: 99%
“…After the first identification of s1/m1 strains showing a higher attributable risk for gastric cancer development, also i1 strains have been demonstrated to be associated with not only dysplastic but also malignant invasive tissue formation [67,69,71]. VacA has an inhibitory effect on GSK3β (glycogen synthase kinase 3-β)-regulated signaling pathways by phosphorylation through an Akt/PI3K (phosphatidylinositol-3-kinase)-mediated pathway, which leads to β-catenin release and furthermore modulation of apoptosis and cell cycle regulation [72,73].…”
Section: H Pylori Virulence Factorsmentioning
confidence: 99%
“…The OR for gastric cancer is about 7.3 in the case of one EPIYA-C segment, and can be up to 51 in the case of two or more segments [67,68]. Relatives of patients with gastric cancer have been shown to carry H. pylori strains with a higher frequency of EPIYA-C segments [69]. Recently, genetic variations in further cagPAI-related genes have been demonstrated to be associated with gastric cancer [70].…”
Section: H Pylori Virulence Factorsmentioning
confidence: 99%